(untitled) (Conferencea, 2022)
In today’s rapidly developing era, there is a real need to develop young people’s analytical thinking in the wide-spread information space. In turn, "problematic task" serves as a way of creating a specific problem situation and can be created orally or in writing in the context of educational activities and taking into account the capabilities and needs of educational subjects. The concept of "task" itself has different meanings in psychological and pedagogical sciences.